(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indigenous people are independent cultural groups inextricably depending on their lands and natural resources and they claim them to be their own. They are experts in sharing and preserving their ancestral land ties from generation to generation. However their preserved indigenity is exploited by the unlawful intensions of the Europeans. Lee Maracle, an indigenous writer of Canada, in her debut novel Bobbi Lee: Indian Rebel, mainly focuses on the lives of the First Nations people of Canada. This paper unravels how the chronological events like European discovery, colonial expansion, implemented government policies, shifted cultivation, population explosion, commercial exchange, diversified economies and individual ownership are exposed by Lee Maracle and the hidden agenda of the Europeans. The paper attempts to analyse Bobbi Lee: Indian Rebel to uncover the divulging information about Canada whose natives are tormented and exploited by European colonisers in terms of advancement and prosperity.